(untitled) (Sains Humanika, 2011)
This study was conducted to measure the moderating role of attidude towards money on the relationship between job satisfaction and voluntary turnover. A survey research method was employed to gather 118 usable questionnaires from employees who have worked in a city based local authority in Sabah, Malaysia. The outcomes of testing research hypotheses hierarchical regression analysis showed two important findings: First, interaction between intrinsic job satisfaction and attitude toward money significantly correlated with voluntary turnover. Secondly, interaction between extrinsic job satisfaction and attitude toward money insignificantly correlated with voluntary turnover. Statistically, this result confirms that positive attitude towards money can motivate employees who have high instrinsic job satisfaction to stay in the organization. Conversely, positive attitude towards money cannot motivate employees who have high extrinsic job satisfaction to stay in the organization. This study confirms that attitude towards money does act as a partial moderating variable in the job satisfaction model of the studied organization. In addition, discussion, implications and conclusion are elaborated.